2017
DOI: 10.1371/journal.pone.0171822
|View full text |Cite
|
Sign up to set email alerts
|

Novel CD28 antagonist mPEG PV1-Fab’ mitigates experimental autoimmune uveitis by suppressing CD4+ T lymphocyte activation and IFN-γ production

Abstract: Autoimmune Uveitis is an important chronic inflammatory disease and a leading cause of impaired vision and blindness. This ocular autoimmune disorder is mainly mediated by T CD4+ lymphocytes poising a TH1 phenotype. Costimulatory molecules are known to play an important role on T cell activation and therefore represent interesting therapeutical targets for autoimmune disorders. CD28 is the prototypical costimulatory molecule for T lymphocytes, and plays a crucial role in the initiation, and maintenance of immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
1
5
0
1
Order By: Relevance
“…This molecule acts as a non-crosslinking CD28 antagonist ( 15 , 16 ) and was chosen because its administration in vivo was not associated with severe immunotoxicity, neither in baboons or non-human primates nor in a trans vivo NOD/SCID mouse model ( 15 , 17 ). Moreover, it prevented organ rejection in a preclinical renal transplantation model and downmodulated autoimmunity in collagen-induced arthritis, experimental autoimmune encephalomyelitis, and uveitis models ( 18 22 ). Finally, it had shown safety and tolerability in a recently completed phase I clinical trial ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…This molecule acts as a non-crosslinking CD28 antagonist ( 15 , 16 ) and was chosen because its administration in vivo was not associated with severe immunotoxicity, neither in baboons or non-human primates nor in a trans vivo NOD/SCID mouse model ( 15 , 17 ). Moreover, it prevented organ rejection in a preclinical renal transplantation model and downmodulated autoimmunity in collagen-induced arthritis, experimental autoimmune encephalomyelitis, and uveitis models ( 18 22 ). Finally, it had shown safety and tolerability in a recently completed phase I clinical trial ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with each individual drug had no effect. This contrasted with data collected in other mouse and non-human primate models of autoimmunity, such as experimental autoimmune uveitis (EAU), EAE and CIA, where selective CD28 blockade effectively altered effector T cell responses and reduced disease severity [7,8,11]. A major difference between these models and the type 1 diabetes NOD mouse model is that they are induced in naive animals on administration of antigen with adjuvant.…”
Section: Discussionmentioning
confidence: 79%
“…Using EAU to mimic human AIU, Papotto and colleagues showed that administration of mPEG PV1 Fab’ (referred to as PV1 hereafter) during the initial phases of disease decreased ocular tissue damage and disease incidence [76], corroborating previous findings that pointed to B7/CD28 blockade as a promising immunotherapeutic strategy for EAU [77]. The observed reduction in ocular inflammation was accompanied by a decrease in the activation profile of CD4 + and CD8 + eye-infiltrating T lymphocytes, and T cells from secondary lymphoid organs also displayed a decrease in CD69, CD25, PD-1, and Tim-3 activation markers [76]. Accordingly, Th1 and Th17 cell numbers in the draining lymph nodes were lower in PV1-treated mice when compared with their untreated counterparts.…”
Section: Autoimmune Uveitis Modelmentioning
confidence: 99%
“…Accordingly, Th1 and Th17 cell numbers in the draining lymph nodes were lower in PV1-treated mice when compared with their untreated counterparts. Of note, regulatory T cells (T reg ) were also decreased in the secondary lymphoid organs after PV1 administration [76], suggesting that the overall reduction in T cell activation and cytokine production is not T reg -dependent, and does not result from anergy. In fact, antigen-specific restimulation of draining lymph node cells in the presence of PV1 resulted in decreased IFN-γ production, indicating that CD28 blockade by PV1 impairs TH1 lymphocyte ability to secrete cytokines upon antigen reencounter [76].…”
Section: Autoimmune Uveitis Modelmentioning
confidence: 99%